The Apocalyptic Visions in the Poems of SP Lohani, GM Hopkins and VS Rai - Parajuli, Bishwo Raj (English Language Teaching Perspectives, 2022)
This article explores some textual and contextual evidences on how Shreedhar Lohani’s ‘Gaia’, G.M. Hopkin’s ‘God’s Grandeur’, and V.S. Rai’s ‘Corona Says’ reveal figures of speech and their underlying suggestions with current environmental crisis, specially focusing on the topics of contemporary environmental discourse related to environmental apocalypticism or catastrophic changes. Relevant environmental, ecological and mythical perspectives have been incorporated to substantiate the argument. The discussion integrates ideas from theoretical insights, textual evidences, contextual cases and views of the inhabitants of affected areas. The discussion critically reads the texts with regards to the claim and key theoretical concepts like Gaia as Earth mother, the arcadias in nature, degraded landscapes like Brownfields, environmental as well as mythical apocalypticism, nature as instrument to gratify human needs and desires and other relevant outlooks. Based on the findings of analysis, the conclusion of the discussion cogently establishes the argument rather than forming certitudes on the poems. The selected texts suggest that the anthropocentric rational framework and a serious self-destructive denial of ecological limits is leading us to eco-catastrophic ends. So, it’s high time we give up our chauvinism and live in harmony with nature and fellow creatures. The conclusion is expected to open avenues for further discussion as well as contestation on the same or similar discourses.